The story of your dog : a straightforward guide to a complicated animal : learn the surprising connections between your unique dog's breed, behaviors, evolution, and genetics to communicate better, train easier, and build a lasting bond - McMillan, Brandon (Harper One, an imprint of HarperCollinsPublishers, 2022)
"Most dog owners know the truth-- their dogs are totally incompatible with the modern world. Instincts like herding, chasing, and protecting have no natural outlet and frequently result in chewing, barking, nipping, jumping, lunging, and worse. However, as McMillan argues in these pages, the solution isn't as simple as mastering "sit" and "stay". No matter what kind of dog you have, no matter how old or young, or well-trained or well-bred, your beloved companion is strongly influenced by his or her DNA. The result of these genetic distinctions shows up in every inch and action-- from the size and shape of a dog's head (and the brain inside it) to the length and curve of his tail, from the texture of her fur to the webbing (or lack of webbing) between her toes. It's in their lung capacity, their tolerance for heat and cold, their appetites for food and exercise, and whether and how they bark. It goes beyond their structure and deep into their psychological profiles. Perhaps you're lucky enough to have a dog with more than a few breeds mixed in, which makes this information all the more crucial to know and understand. In The Story of Your Dog, McMillan breaks down why your dog acts the way he does, so you can train better and easier, with fewer missteps and miscommunications, and bond in ways you never thought possible. It is an invitation to get to know the sometimes frustrating but always incredible dog at the other end of the leash."--page 2 of cover.